Secondary Level Teachers’ Job Satisfaction in Nepal: A Case of three Districts - Chapagai, Shiva Dutta (KMC Journal, 2023)
This study investigated the job satisfaction level of the secondary level teachers of Tanahun, Kaski and Chitwan districts in Nepal. Basing on the survey design of quantitative research, method, data were collected from 292 respondents through structured questionnaires. Five-point Likert-scale technique was used for collecting data. Descriptive statistics, independent-samples t-test, and one-way ANOVA test were used to analyze the data. This study found that the majority of respondents were satisfied with the job nature, pay and fringe benefits, members’ cooperation to work, and the working environment of a school and in the teaching profession. However, they were not satisfied with the mechanism of school supervision and promotion process and procedures, independent F-test and t-test are satisfied with a 95% confidence level. There is no meaningful difference (P-value is less than 0.05) between teaching experience, gender, and job satisfaction level. The policy makers should consider the view of employee about their job perception at the time of making rules and regulation related to the employee, the government should make clear rules and regulation related to promotion process.